EMERGENCY RELIEF MATERIALS ADMINISTRATION AND THE WELFARE OF INTERNALY DISPLACED PERSONS IN MAIDUGURI, BORNO STATE - YUSUF, MUHAMMAD SANI; BARKA, HADIZA MUHAMMAD; UMARU, DEBORAH (Innovare Journal of Social Sciences, 2023)
The study focuses on interrogating emergency relief materials administration and the welfare of internally displaced persons (IDPs) in Maiduguri. Internal displacement has rendered over 2 million people in Nigeria homeless, with Maiduguri hosting over 1.6 million as at May, 2021. These IDPs are camped by governments across the nation, while some of them went to stay with friends or relatives who reside in neighboring local government areas or states. The study adopts Joseph’s prebendalism theory which explains a situation in which public officials use their position of trust to amass wealth through criminal means. Both primary and secondary sources of data collection were used. The primary source employed the use of Focus Group Discussion from among the IDPs in selected camps as well as IDPs outside camps. Key Informants Interviews with government officials at NEMA and SEMA, etc., was used; while online newspapers, radio reports, etc., served as secondary sources. The findings of the study show that some officials of the national and state emergency management agencies divert emergency relief materials meant for IDPs for their personal gains. It also shows that this diversion of relief materials affects the general welfare of the IDPs. The study recommends among other things that an agency should be created to coordinate and monitor the activities of the national and state emergency management agencies and all other agencies and NGOs with regard to the collection and distribution of relief materials and rehabilitation of IDPs.